Cassandra in reverse ebook - Smale, Holly (2023)
A REESE'S BOOK CLUB PICK from the author of the GEEK GIRL series, now on NETFLIX! "Fascinating...witty...self-deprecating...We meet Cassandra on the worst day of her life. She's getting fired, her boyfriend dumps her, and her roommates hate her. On that same day, she discovers she has the power to go back in time. You'd think you would know how this book is going to end, but it really surprised me. There's a twist at the end that I did not see coming!" —Reese Witherspoon (Reese's Book Club June '23 Pick) If you had the power to change the past...where would you start? Cassandra Penelope Dankworth is a creature of habit. She likes what she likes (museums, jumpsuits, her boyfriend, Will) and strongly dislikes what she doesn't (mess, change, her boss drinking out of her mug). Her life runs in a pleasing, predictable order...until now. She's just been dumped. She's just been fired. Her local café has run out of banana muffins. Then, something truly unexpected happens: Cassie discovers she can go back and change the past. One small rewind at a time, Cassie attempts to fix the life she accidentally obliterated, but soon she'll discover she's trying to fix all the wrong things. "A great read-alike for The Rosie Project by Graeme Simsion, Oona Out of Order by Margarita Montimore, and The Boys by Katie Hafner." —Booklist (STARRED)